(untitled) (Al-Academy, 2018)
fashion designers who have benefited greatly from the mobilization of ancient aesthetic ideas in the heritage of the people and guaranteed in their productions so that there is no change In the aesthetic value created by the designers of the research in the ancient heritage to find new signs that reflect the connection of man to the present as the aesthetic value of all the man created by the designs of fabrics and fashion through the ages The problem of research was determined in the absence of a precise understanding of the nature of classical thought in fashion and the absence of a clear perception of the sustainability of this thought in contemporary fashion. Hence the importance of research in the development of applied and operational capacities For the designers of fashion in different schools and trends of the concepts of generation that shows new possibilities that lead to the growth and intellectual and aesthetic recovery and the activation of the capabilities of designers. The research aims to identify the new vision of the classic in fashion design Contemporary